In vivo and in vitro bioactivity of a "precursor of apatite" treatment on polyetheretherketone. (June 2019) - Masamoto, Kazutaka; Fujibayashi, Shunsuke; Yabutsuka, Takeshi; Hiruta, Tomoko; Otsuki, Bungo; Okuzu, Yaichiro; Goto, Koji; Shimizu, Takayoshi; Shimizu, Yu; Ishizaki, Chihiro; Fukushima, Keito; Kawai, Toshiyuki; et al.
Graphical abstract: Abstract: We recently developed a surface treatment, "precursor of apatite" (PrA), for polyetheretherketone (PrA-PEEK) via a simple, low-temperature process aiming to achieve stronger and faster adhesion to bone. The treatment involves three steps: H2 SO4 immersion, exposure to O2 plasma discharge, and alkaline simulated body fluid (alkaline SBF) treatment. This method produces homogeneous fine particles of amorphous calcium phosphate on the PEEK, and we confirmed that PrA-PEEK had excellent apatite formation ability in an SBF immersion test. In the present study using PEEK implants in rabbit tibia, mechanical tests, and histological and radiological analyses revealed that PrA provided the PEEK substrate with excellent bone-bonding properties and osteo-conductivity at early stages (4 and 8 weeks), extending to 16 weeks. In vitro study using MC3T3-E1 cells revealed via XTT assay that PrA on the PEEK substrate resulted in no cytotoxicity, though PrA treatment seemed to suppress gene expression of integrin β-1 and Alp after 7-day incubation as shown by real-time PCR. On the whole, PrA treatment succeeded in giving in vivo bone-bonding properties to the PEEK substrate, and the treatment is a safe and promising method that can be applied in clinical settings. There was an inconsistency between in vivo and in vitro bioactivity, and this discrepancy indicated that apatite formation does not always need activation of osteoblasts at very early stage and that optimal conditions at cell and organism level may be different. Statement of Significance: Polyetheretherketone (PEEK) is an attractive engineering polymer used for spine and dental surgery. To further improve clinical outcome of PEEK-based materials, we developed "Precursor of apatite" (PrA) treatment on the PEEK surface to confer bone-bonding properties. The advantages of this treatment are that it does not require high-temperature processing or special chemicals, and it is inexpensive. The present study clarified excellent in vivo bone-bonding property of PrA treatment. In addition, the results revealed important insights indicating that optimal conditions, especially wettability and crystallinity in calcium phosphate, differ at cell and organism levels. Moreover, our results indicated that prediction of in vivo bioactivity should be done in combination with multiple in vitro tests.